RANKING OF TOURIST DESTINATIONS WITH MULTI-CRITERIA DECISION MAKING METHODS IN BOSNIA AND HERZEGOVINA - Göksu, Ali; Kaya, Seniye Erdinç (Economic Review: Journal of Economics and Business, 2014)
Developments in communication and transportation technology have increased access to formerly distant destinations in an unprecedented way. Tourist centers develop new strategies to increase their share in this growing market. Travel agencies put up advertisements to keep their present customers and attract the new ones. Because customers have a wide array of alternatives to choose from, appropriate strategies should be developed to persuade customers during their decision-making process. In this study, six tourist centers in Bosnia and Herzegovina (BiH) were analyzed according to the criteria used by customers as they decide on their vacation destinations. The data were collected from four travel agencies by means of focus group interviews. The interview data were analyzed with Fuzzy Analytic Hierarchy Process (FAHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), which are methods of multi-criteria decision making (MCDM). The criteria used in the study were determined by the teams in the agencies that were the experts in the local conditions of the country. The aim of the study was to extract the main criteria that influence tourists to visit BiH and provide a ranking of tourist destinations in terms of popularity.